2016
DOI: 10.1063/1.4967406
|View full text |Cite
|
Sign up to set email alerts
|

Nucleation and growth mechanisms of Al2O3 atomic layer deposition on synthetic polycrystalline MoS2

Abstract: Two-dimensional (2D) semiconducting transition metal dichalcogenides (TMDs) are of great interest for applications in nano-electronic devices. Their incorporation requires the deposition of nm-thin and continuous high-k dielectric layers on the 2D TMDs. Atomic layer deposition (ALD) of high-k dielectric layers is well established on Si surfaces: the importance of a high nucleation density for rapid layer closure is well known and the nucleation mechanisms have been thoroughly investigated. In contrast, the nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 42 publications
2
50
0
Order By: Relevance
“…as well as nanometer scalability (to reduce their effective oxide thickness "EOT" for enhanced gate control over the MoS 2 channel). The interested reader is directed to various literature reports for further reading on these topics [317][318][319][320][321][322][323][324][325][326][327][328][329][330][331][332][333]. The focus of the following discussion is on the influence of dielectric engineering on important device parameters, such as doping, carrier mobility, ON-currents and contact resistance, and how dielectric engineering can be used to help enhance the performance of MoS 2 -based devices.…”
Section: Role Of Dielectrics In Doping and Mobility Engineeringmentioning
confidence: 99%
“…as well as nanometer scalability (to reduce their effective oxide thickness "EOT" for enhanced gate control over the MoS 2 channel). The interested reader is directed to various literature reports for further reading on these topics [317][318][319][320][321][322][323][324][325][326][327][328][329][330][331][332][333]. The focus of the following discussion is on the influence of dielectric engineering on important device parameters, such as doping, carrier mobility, ON-currents and contact resistance, and how dielectric engineering can be used to help enhance the performance of MoS 2 -based devices.…”
Section: Role Of Dielectrics In Doping and Mobility Engineeringmentioning
confidence: 99%
“…The hole-doping is likely caused by local oxidation of underlying single layer MoTe2 and/or hole injection from top high working function oxide film (MoOx, with x<3) [3][4][5] . However, we rule out the possibility of local oxidation by transport measurement of oxidized monolayer MoTe2.…”
Section: Supplementary Textmentioning
confidence: 99%
“…Our findings point to a simple and effective strategy for growing homogenous surface oxide film on MoTe2, which is promising for several purposes in metal-oxidesemiconductor transistor, ranging from surface passivation to dielectric layers. 3 Thin oxide layer is critical for the development of modern semiconductor manufacturing technology, which has been widely adopted for insulating in active devices, for physical masking in patterning process, for passivation to protect function materials from contamination 1 . SiO2 or atomic-layer-deposited (ALD) Al2O3 has been widely adopted as dielectric or insulating layers in transitional metal dichalcogenides (TMDs)-based complementary metal oxide semiconductor (CMOS) devices 2,3 .…”
mentioning
confidence: 99%
“…Thus, the top surface consists of the WS2 crystal basal planes and grain boundaries. It has been observed that the crystal basal planes of 2D materials typically have a low reactivity for ALD [36][37][38] . Instead, the chemisorption of ALD precursors on 2D materials can occur at line defects and grain boundaries 38 .…”
Section: A Substrate Enhanced Growth Of Ws2 Peald On Amorphous Al2o3mentioning
confidence: 99%